Common words in Muslim-Christian dialogue : a study of texts from the common word dialogue process - Horsfjord, Vebjorn L. (Currents of Encounter, 2017)
In Common Words in Muslim-Christian Dialogue Vebjørn L. Horsfjord offers an analysis of texts from an international dialogue process between Christian and Muslim leaders. Through detailed engagement with the Muslim dialogue letter A Common Word between Us and You (2007) and a large number of Christian responses to it, the study analyses the dialogue process in the wake of the Muslim initiative and shows how the various texts gain meaning through their interaction. The author uses tools from critical discourse analysis and speech act analysis and claims that the Islamic dialogue initiative became more important as an invitation to Muslim-Christian dialogue than as theological reflection. He shows how Christian leaders systematically chose to steer the dialogue process towards practical questions about peaceful coexistence and away from theological issues.